A Spatially Integrated Dissolved Inorganic Carbon (SiDIC) Model for Aquatic Ecosystems Considering Submerged Vegetation. Issue 2 (16th February 2023) - Nagatomo, K.; Nakayama, K.; Komai, K.; Matsumoto, H.; Watanabe, K.; Kubo, A.; Tada, K.; Maruya, Y.; Yano, S.; Tsai, J. W.; Lin, H. C.; Vilas, M.; et al.
Abstract: Net ecosystem production (NEP) by submerged aquatic vegetation plays a substantial role in capturing atmospheric carbon dioxide into aquatic ecosystems. In lakes and estuaries, the net uptake of carbon dioxide by submerged aquatic vegetation is mediated by stratification of the water column which suppresses the vertical flux of carbon dioxide between the upper and lower layers. The presence of submerged aquatic vegetation can also affect the strength of stratification such that the interactions between vegetation, stratification, and NEP can moderate the carbon dioxide emissions. Since stratification can occur in lakes and estuaries, there is need for a new numerical approach able to consider the effect of submerged aquatic vegetation on stratification, NEP, and carbon dioxide. This study aims to develop a model to investigate how stratification, mediated by vegetation density and flexibility, affects the partial pressure of carbon dioxide ( p CO2 ) and dissolved inorganic carbon (DIC). After initial parameterization of coefficients based on experimental work, horizontal and vertical variations in DIC were successfully modeled by a spatially (horizontally) integrated DIC (SiDIC) model, which was validated with field observations from an estuarine and freshwater lake case study. The SiDIC model was able to reproduce the p CO2 changes between daytime and nighttime throughout the water column. Sensitivity tests showed that the fluctuation of p CO2 was controlled by the suppression of stratification due to the density of submerged aquatic vegetation. The results highlight the importance of resolving vegetation‐induced stratification when modeling the carbon budget within freshwater lakes and coastal environments. Plain Language Summary: The key idea of the present study is that "vegetation‐induced stratification" suppresses vertical mixing in lakes and plays a substantial role in determining how much atmospheric carbon dioxide exchanges with the water. Field observations in Komuke Lagoon and Lake Monger were used to create a representative data set for understanding dissolved inorganic carbon (DIC) metabolism in coastal and freshwater lake ecosystems, respectively. A spatially integrated DIC model was then created to reveal that the fluctuation of partial pressure of carbon dioxide was controlled by the suppression of stratification which is related to the density of submerged aquatic vegetation. The results demonstrate the effect of submerged aquatic vegetation on the vertical mixing of DIC, with implications for our understanding of carbon capture within aquatic ecosystems. Key Points: Submerged vegetation promotes stratification in shallow freshwater and coastal lakes which can impact net CO2 capture Model results demonstrate that vegetation properties mediate the diurnal p CO2 excursion by influencing vertical exchange with the canopy The results highlight the importance of resolving vegetation‐mediated changes in mixing when estimating carbon uptake by submerged canopies